Alluvial Platinum-Group Minerals in Southern New Zealand (The Australasian Institute of Mining and Metallurgy, 1995)
Platinum-group minerals (PGM) are recorded from a number of localities along theWaiau River, western Southland, and the south coast of the South Island, New Zealand. At each locality, small amounts of PGMs were recovered as by-products of historical gold mining operations. During the period 1890-1950 an estimated 1000-2000 oz. of æplatinumÆ were recovered from the region, the only area within New Zealand where PGM have been commercially exploited. The PGM suite of southern New Zealand consists of Pt-Fe alloys, IPGE (iridium subgroup, platinum-group elements) alloys, sperrylite (PtAs2), cooperite (PtS) and braggite ((Pt,Pd)S). The composition of Pt-Fe alloy exhibits considerable variation and two compositional populations are recognised. Some Pt-Fe alloy grains are chemically zoned. Iridium is the most abundant IPGE alloy phase and often contains considerable Pt, in contrast to osmium and ruthenium alloys. Cooperite and braggite grains are characterised by extremely low concentrations of Ni.   Exsolution of osmium and iridium from Pt-Fe alloy and Pt-Fe alloy from iridium is observed Several PGM host mineral inclusions which vary from single to poly-phase, display rounded to equant outlines and range in diameter from greater than 100 ¦m to less than 5 ¦m. Olivine and Ni-sulphide inclusions are only present within IPGE alloys. Pt-Fe alloy, cooperite, braggite and sperrylite host Cu-Fe sulphides, a wide variety of PGM, clinopyroxene, amphibole, magnetite and plagioclase within inclusions. Sperrylite also hosts Pd bismuthiotellurides, gold and several potassium-rich silicate phases. Similarities in inclusion phases and mineral chemistry from several localities suggest that the PGM are derived from a single (as yet unidentified), probably calc-alkaline magmatic source. This source is situated somewhere along the margins of the western Southland sedimentary basin where PGM liberated by erosion are transported down the Waiau River and dispersed eastwards along the coast by strong longshore currents.